2014
DOI: 10.12659/msmbr.890247
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of endodontic irrigants in vitro

Abstract: Background:Cytotoxicity of root canal irrigants is important due to their close contact with host tissues. The aim of this study was to assess the cytotoxic effect of NaOCl 3%, Chx 2%, and MTAD on rat periodontal ligament fibroblasts, at 0.1 and 100 µl/mL, using WST-1 colorimetric method. Material/Method:Rat ligamental fibroblasts were exposed to the irrigants and their viability was assessed after 1, 24, 48, and 72 h. The measurements were determined using WST-1 assay, using a micro ELISA reader. Results:At 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
5
1
Order By: Relevance
“…At concentration of 100 μL/mL and 24-hour interval, both solutions were highly cytotoxic, but CHX toxicity was less than that of NaOCl, which is consistent with the present study. In contrast to the results of the present study, the NaOCl toxicity was reported to be higher than that of CHX at 48 and 72-hour intervals (21). This inconsistency in results could be due to the difference in the concentrations of studied solutions, the evaluation method and the type of cells studied.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At concentration of 100 μL/mL and 24-hour interval, both solutions were highly cytotoxic, but CHX toxicity was less than that of NaOCl, which is consistent with the present study. In contrast to the results of the present study, the NaOCl toxicity was reported to be higher than that of CHX at 48 and 72-hour intervals (21). This inconsistency in results could be due to the difference in the concentrations of studied solutions, the evaluation method and the type of cells studied.…”
Section: Discussioncontrasting
confidence: 99%
“…It should also be noted that in vivo, the materials are neutralized quickly and removed by phagocytes and the lymphatic and vascular systems, so they are less harmful in clinical conditions than at same concentrations in in vitro studies. In vitro measurements of toxicity are only at cell level, so the results of the present study cannot be compared with the results of in vivo studies directly (21). Future studies should be conducted on root canal irrigants in animals and then in humans to assess their cytotoxicity and in vivo biocompatibility.…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, LSM evaluation showed heavy changes in the cells’ morphologies ( Figure 5 e). The cytotoxic effects of CHX on oral fibroblasts are already well known [ 25 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reports on sodium hypochlorite cytotoxicity seem somehow contradictory. Sodium hypochlorite—the active substance in the PS—exerts a negative impact on non-human MSCs [ 27 , 28 ] or on periodontal ligament fibroblasts [ 45 ]. Additionally, SEM analyses reported an inhibitory effect of 0.5 mg/mL sodium hypochlorite on cell adhesion [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of cytotoxicity appreciation from this perspective could be considered a limitation of our study. The continuous secretion of the gingival crevicular fluid eliminates the antimicrobials from the subgingival areas [ 51 ], which renders living tissues less susceptible to the toxic effects of drugs than cultured cells [ 45 ]. The deleterious effect of the commercial products, and mostly of PF on gMSCs, warrants caution when used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%